SIMULASI DINAMIKA BENDA JAMAK INTERAKSI RODA-REL UNTUK LOKOMOTIF LANGSIR DI JALUR BERPUNTIR - Alvian Iqbal Hanif Nasrullah; Prasetya Adi Nugraha (Scientific Journal of Mechanical Engineering Kinematika, 2024)
The effects of track twist on a shunter locomotive, a subject less explored compared to high-speed and freight trains, are investigated to extend knowledge of wheel-rail interaction. The study focuses on the impact of a 5% track twist on spring forces experienced by train wheels, addressing key issues such as derailment potential and wheel-rail contact loss. By analyzing the Nadal ratio and wheel lift under low-speed conditions (10-20 km/h), typical for shunter locomotives, the study provides new insights into operational safety. Multibody dynamics simulation with a simplified two-axle locomotive model shows that, despite challenging twisted track conditions, both Nadal ratio and wheel lift remain within safe limits, indicating a low risk of derailment. While these findings align with safety criteria established for other types of rail vehicles, the focus on shunter locomotives under such conditions represents a novel contribution to the field, filling a gap in existing literature. The study’s limitations, including model simplifications and the exclusion of real-world complexities, highlight the need for further validation and research to improve understanding of wheel-rail dynamics across varied operational environments.